44th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2003
DOI: 10.2514/6.2003-2003
|View full text |Cite
|
Sign up to set email alerts
|

Design of Composite Layers With Curvilinear Fiber Paths Using Cellular Automata

Abstract: The anisotropic advantageous properties of fiber reinforced composites may not be fully exploited unless the fibers are properly placed in their optimal spatial orientations. This paper investigates application of Cellular Automata (CA) for curvilinear fiber design of composite laminae for in-plane responses. CA use local rules to update both field and design variables in an iterative scheme till convergence. In the present study, displacement update rules are derived using a finite element model governing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This literature was completed with other existing publications and web-based articles gathered through other sources in a less structured manner. Papers related to variable stiffness laminates that were found relevant 1,2,5–11,1330,3252,55–69 (a total of 63 papers) have been analysed to assess whether they perform or develop a set of tasks (Figure 9(a)).…”
Section: Discussionmentioning
confidence: 99%
“…This literature was completed with other existing publications and web-based articles gathered through other sources in a less structured manner. Papers related to variable stiffness laminates that were found relevant 1,2,5–11,1330,3252,55–69 (a total of 63 papers) have been analysed to assess whether they perform or develop a set of tasks (Figure 9(a)).…”
Section: Discussionmentioning
confidence: 99%
“…Setoodeh et al [6] showed that the optimality criteria reduce to the minimization of the complementary strain energy at any point in the domain. Numerical studies show that substantial stiffness improvements can be gained only by reorientation of the orthotropic material in an optimal manner [5][6][7]. However, such a formulation requires repeated transformation of the material properties using the classical trigonometric transformations.…”
Section: Introductionmentioning
confidence: 97%
“…Since results are based on a fixed stress or strain field, structures that are more complex require numerical investigations due to a varying field. Based on this research, Setoodeh et al [13][14][15] used these principles to develop a framework, which uses cellular automata to update local material orientations iteratively including multiple load cases. Given the fact, that only fiber orientations and layer thicknesses are used as design variables, global optima could not be achieved when considering general laminates.…”
Section: Introductionmentioning
confidence: 99%